Free to Be Foolish : Politics and Health Promotion in the United States and Great Britain - Leichter, Howard M. (Book collections on Project MUSE., 2014)
Each of us is, to a certain extent, dangerous to his or her own health, but how far do we want the government to curb our freedom to be ""foolish""? In a look at such highly charged health issues as smoking, alcohol, road safety, and AIDS, Howard Leichter analyzes the efforts of the United States and Great Britain to confront the seemingly constant tension involved with this question. Leichter contends that both governments are now paying less attention to providing access to health care and more to forcing or encouraging people to change their behavior. The result has been a transformation.